A systematic literature review on the influence of entrepreneurial competence on business success - Salong, Amjad; Ansiska, Paisal (Indonesian Indovisi Institute, 2025)
This study aims to conduct a Systematic Literature Review (SLR) to analyze the influence of entrepreneurial competency on business success, examining the roles of business innovation, managerial ability, and entrepreneurial orientation as intermediary variables. The background of this study departs from findings indicating that entrepreneurial competency does not always have a direct impact on business performance, and that a more comprehensive understanding of the mechanisms mediating these two variables is needed. This study examines scientific articles published between 2014-2024 that address the themes of competency, innovation, management, entrepreneurial orientation, and business performance. The methods used include identification, selection, and critical analysis of articles using the PRISMA protocol, with data analysis conducted thematically to identify patterns of relationships between variables. The main findings indicate that entrepreneurial competency positively affects business success when mediated by innovation, managerial ability, and entrepreneurial orientation. Innovation creates added value, managerial ability improves operational effectiveness, and entrepreneurial orientation directs competency toward proactive, innovative strategic actions. This study provides theoretical contributions by mapping a more complete structure of the relationship between competency and business performance, as well as practical contributions for business actors, educational institutions, and policymakers in designing entrepreneurial capacity-building programs.